Analysis and Simulation of The Effects That Cause Fatigue in the Frame Structure 308 of the Uh-60 Helicopter - Florez Zuluaga, Jimmy Anderson; Márquez Atrio, Andrés; Ayala Angel, Andres; Carreño Hernández, Carlos Jahir (Ingeniería Solidaria, 2019)
Introduction: This is a product of the research “Study of operational maneuvers for the detection of structural fatigue in the UH-60 helicopter”, developed through COLCIENCIAS project number 56742, at the Colombian Air Force-Aerospace Technology Development Centre for the Defense - CETAD, during 2017-2019.The objective of the project was to design and develop a system that would allow studying the strain generated by operational maneuvers and the relation between them and the structural fatigue of frame 308 of the UH-60.Methodology: The project was based on the integration of strain and vibration data from the helicopter’s frame 308 instrumentalization to development a relevant simulation and analysis.Results: In the first instance, the data collection was synchronized with the flight maneuvers, identifying the strain generated in each position. This helped establish the range of the loads on the beam during operational maneuvers.Conclusions: In this project, a series of sensors and data acquisition and recording devices were integrated into the aircraft in order to identify the maneuvers that generate strain in frame 308, based on the use of the manufacturer's manuals and engineering processes.Originality: This document formulates data from possible situations for the first time, because there is no history of literature on the study, characterization or materials on frame 308 of the UH-60 helicopter.Limitations: Insufficient public information about the UH-60 aircraft.
Keywords: UH-60; simulation; frame 308; Dot cloud; XFEM; material characterization; fatigue; damage evolution; structural efforts